2013
DOI: 10.1111/jbi.12150
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and evolutionary history of the Neotropical genus Saltator (Aves: Thraupini)

Abstract: Aim We reconstructed the biogeographical and evolutionary history of Saltator by producing a robust phylogenetic hypothesis that we used to evaluate the geographical origins of this genus, and assessed the potential influence of major Neotropical biogeographical features on the origin of lineages within this assemblage (i.e. phylogroups). Location Neotropics. Methods Our phylogenetic reconstruction is based on newly sequenced mitochondrial DNA data representing all known species of Saltator. This phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…1). One exception was Saltator striatipectus, which contains multiple phylogeographic lineages that are distributed in northern South America and Central America (Chaves et al 2013). The pairs were as follows, with the Marañ on Valley taxon presented first followed by the Tumbesian taxon: Thamnophilus bernardi shumbae -T. b. bernardi; Melanopareia maranonica -M. elegans; Campylorhynchus fasciatus fasciatus -C. f. pallescens; Mimus longicaudatus maranonicus -M. l. longicaudatus; Arremon abeillei nigriceps -A. a. abeillei; Saltator striatipectus peruvianus -S. s. immaculatus.…”
Section: Taxon Samplingmentioning
confidence: 99%
“…1). One exception was Saltator striatipectus, which contains multiple phylogeographic lineages that are distributed in northern South America and Central America (Chaves et al 2013). The pairs were as follows, with the Marañ on Valley taxon presented first followed by the Tumbesian taxon: Thamnophilus bernardi shumbae -T. b. bernardi; Melanopareia maranonica -M. elegans; Campylorhynchus fasciatus fasciatus -C. f. pallescens; Mimus longicaudatus maranonicus -M. l. longicaudatus; Arremon abeillei nigriceps -A. a. abeillei; Saltator striatipectus peruvianus -S. s. immaculatus.…”
Section: Taxon Samplingmentioning
confidence: 99%
“…The situation is notably improving for birds (e.g. Patané et al ., ; Ribas et al ., ; Patel et al ., ; Chaves et al ., ; Batalha‐Filho et al ., ), but studies of low‐vagility (small, nonvolant, stenotopic) organisms that might closely track biomes or other landscape units over time are still much to be desired. Small didelphid marsupials of the genus Monodelphis Burnett, 1830, are good candidates for such analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, comparing the evolutionary histories of multiple codistributed taxa may improve our understanding of how and when species originated (Chaves et al, 2013;Batalha-Filho et al, 2014). Molecular phylogenies of extant taxa provide an indirect record of speciation events, from which temporal patterns of lineage divergence can be reconstructed (Barraclough & Nee, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…631-632. Phylogenetic analysis of mitochondrial DNA sequences (Chaves et al 2013) has shown that the linear sequence of species in the genus Saltator does not accurately reflect their evolutionary relationships.…”
Section: Spermophila Corvinamentioning
confidence: 99%
“…Under the heading Genus SALTATOR Vieillot, add the following to the end of the existing Notes: Linear sequence of species follows Chaves et al (2013). Notes.…”
Section: Spermophila Corvinamentioning
confidence: 99%